Abordaje biopsicosocial de la mutilación genital femenina en la Gambia - Jorge Humberto Díaz Rodríguez; Yosleiny Díaz Reyes; Ayde María Pérez Quiala (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2022)
This review work shows how, according to the latest UNICEF data, around 3 million girls and women each year are subjected to some type of Female Genital Mutilation (FGM) in Africa where the social and cultural roots on which FGM is supported and fed back, it is due to the experience of their elders, their own mothers and grandmothers, with confusing religious messages and lax laws. The socialization process that shapes the attitudes of girls and women prepares them to accept pain and suffering as an inevitable part of a woman's life, and as an obligation to fulfill in order to be accepted in their respective societies. However, the women who practice it do not need a justification and when asked, they refer to tradition, religion and aesthetic, health or protection issues. It is necessary to have an anthropological view of the phenomenon to obtain an understanding of its significance that allows to approach the subject with knowledge and respect and thus work to achieve a change in society that leads to the elimination of the causes of violation of the right to health and fight to end the practice of FGM. Therefore, the objective is to expose the practice of Female Genital Mutilation from a biopsychosocial perspective in the Republic of the Gambia, so that it is a useful tool for professionals in contact with the population at risk. The study is developed in the context the University during the period November 2020-February 2021.